Pengaruh Leverage, Profitabilitas, Likuiditas, Dewan Komisaris, Dan Ukuran Perusahaan Terhadap Environmental Disclosure (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022) - Ayyas, Yahya; Ihsan, Budi; Prastya, Hendra (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
This study investigates the effect of financial factors (leverage, profitability, and liquidity), internal company factors (board of directors), and company size on environmental information disclosure in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2022. The research approach used is descriptive quantitative. Data were collected from the company's financial statements and annual reports published on the Indonesia Stock Exchange website. The results of the analysis show that leverage, profitability, liquidity, board of directors, and company size individually have a significant influence on environmental information disclosure. Overall, these factors have a contribution of 32.7% to the disclosure of environmental information, while the rest is influenced by other factors. These results indicate that companies tend to pay more attention to environmental information disclosure when they have better financial ratios and internal structures that pay attention to environmental responsibility. In conclusion, the findings of this study confirm that financial factors and internal factors of the company have an important role in the disclosure of environmental information. The implication of this study is the importance of attention to environmental responsibility in corporate managerial decisions, especially in the context of information disclosure that is increasingly important to stakeholders. Thus, the results of this study provide a better understanding of the factors that influence environmental information disclosure in manufacturing companies, providing a foundation for companies to increase transparency and environmental responsibility in an effort to meet the expectations of society and other stakeholders.